IMPACT OF THE COVID-19 ON THE SPENDING PATTERN AND INVESTMENT BEHAVIOUR OF RETAIL INVESTORS - Siddiqui, Farheen; Raghuvanshi, Anvita; Anant, Srijan; Kumar, Surendra (Indian Journal of Finance and Banking, 2022)
The year 2020 has witnessed the highly infectious disease Corona Virus outbreak impacted across the globe. This unpredictable and unprecedented calamity has pushed economies to struggle and strive. Most of the sectors in the economy were severely hit, which led to financial suffering. There is a paradigm shift in the circular flow of income, which has affected the lifestyle and changed people's spending and investment habits. This study aims to understand how the Covid-19 pandemic has influenced the financial decision-making and investment preferences of retail investors. This research paper also studies the changes in the spending pattern of people during the lockdown due to Covid-19. A sample survey was conducted through a structured questionnaire to determine the impact of the pandemic on individual investment decisions in the city of Lucknow. A random sampling technique has been used to collect the data for the study. The study's findings show that people's lifestyles and spending habits have changed significantly due to the pandemic fear and lockdown. The study also indicates that there has been a shift in the spending preference of people towards healthy products and essentials.JEL Classification Codes: D90, G30, G40, G51, M10.